Wich factors influencing the number of teeth at 12 months of age: a birth cohort study - Ethieli Rodrigues da Silveira; Mariana Gonzalez Cademartori; Thiago Machado Ardenghi; Mariangela Freitas Silveira; Fernando Celso Barros; Marina Sousa Azevedo; Flávio Fernando Demarco (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract: This study aimed to verify, through a longitudinal follow-up, the pre-, peri- and postnatal factors associated with the eruption of deciduous teeth. The study was nested in a Birth Cohort Study conducted in Pelotas, a Southern Brazilian city. Mothers were followed prenatally and their children were followed-up perinatally, at 3 and 12 months of age. The outcome was the number of teeth at 12 months, and exploratory variables included maternal habits and characteristics, anthropometric measures of children and mothers, and socioeconomic and demographic information. Data were collected through interviews with the mother and children's clinical exam. Poisson regression models were used for the analysis. Participants included 4,014 children with a mean number of erupted teeth at 12 months of 5.50. After adjustments, a lower mean number of teeth was observed in children from non-white mothers, early preterm children, and shorter children at birth and at 12 months. A higher number of teeth was observed for mothers with excessive weight gain during pregnancy, mothers who smoked during pregnancy, weightier children at birth and at 12 months, and for children with larger heads at birth and at 12 months. Our findings suggest that maternal and children characteristics influenced primary tooth eruption.